2023
DOI: 10.3390/cells12182242
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the Molecular Mechanisms Driving Electropathology in Atrial Fibrillation: Deployment of RNA Sequencing and Transcriptomic Analyses

Fabries G. Huiskes,
Esther E. Creemers,
Bianca J. J. M. Brundel

Abstract: Despite many efforts to treat atrial fibrillation (AF), the most common progressive and age-related cardiac tachyarrhythmia in the Western world, the efficacy is still suboptimal. A plausible reason for this is that current treatments are not directed at underlying molecular root causes that drive electrical conduction disorders and AF (i.e., electropathology). Insights into AF-induced transcriptomic alterations may aid in a deeper understanding of electropathology. Specifically, RNA sequencing (RNA-seq) facil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 85 publications
(136 reference statements)
0
1
0
Order By: Relevance
“…The general dissection of the molecular changes underlying AF initiation and progress in human bulk right and left atrial tissue has identified pathway changes in mechanotransduction, extracellular matrix remodelling, ion channel signalling, oxidative stress, apoptosis, fibrosis, and structural tissue organization under both developmental and inflammatory signalling. 41 , 42 These profiling studies generally credit the development of AF to deregulation of ion channels, calcium handling, structural remodelling, or autonomic neural regulation, and as such, AF is seen as a consequence of other cardiovascular pathologies. 42 However, the overlap of the results in these studies is not overwhelming at the molecular level, indicating that much remains to be discovered for targeted diagnostics and therapeutics.…”
Section: Genomics and Transcriptomics As Tools For Uncovering Af Mech...mentioning
confidence: 99%
“…The general dissection of the molecular changes underlying AF initiation and progress in human bulk right and left atrial tissue has identified pathway changes in mechanotransduction, extracellular matrix remodelling, ion channel signalling, oxidative stress, apoptosis, fibrosis, and structural tissue organization under both developmental and inflammatory signalling. 41 , 42 These profiling studies generally credit the development of AF to deregulation of ion channels, calcium handling, structural remodelling, or autonomic neural regulation, and as such, AF is seen as a consequence of other cardiovascular pathologies. 42 However, the overlap of the results in these studies is not overwhelming at the molecular level, indicating that much remains to be discovered for targeted diagnostics and therapeutics.…”
Section: Genomics and Transcriptomics As Tools For Uncovering Af Mech...mentioning
confidence: 99%